IMPLEMENTASI PENGARUSTAMAAN GENDER DALAM PEMBANGUNAN DAERAH DI KABUPATEN BOVEN DIGOEL - Yunita Nensy Uniplaita (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Implementation of Gender Mainstreaming In Regional Development In Boven Digoel Regency. Gender mainstreaming is government task to do that gender must be integrated into all activities done by the government focusing on development such as policies,program, and activities. This research was conducted by using qualitative descriptive to analyze in how the implementation of gender mainstreaming (Regent Regulation Number 35 of 2019) was implemented in accordance with Van Meter and Van Horn’s policy implementation mode. This research found gender mainstreaming has not been implemented optimally due to lack of human resources, intently communication to targeted as well as lack of understanding and attitude implementing of policy